2023
DOI: 10.1111/bdi.13300
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and risk of cardiovascular disease, dementia and venous thromboembolism

Abstract: ObjectiveTo determine if long‐term lithium treatment is associated with protective effects or increased risk of vascular, neurological, and renal disorders.MethodsUsing nationwide registers, we included all citizens of Finland with dispensations of lithium for three or more consecutive years between 1995 and 2016. We identified 9698 cases and matched 96,507 controls without lithium treatment. Studied outcomes were vascular, neurological, renal disorders, and suicide. Analyses were performed applying Cox propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The use of lithium therapy has a protective effect on reducing the risk of developing dementia, which is consistent with the conclusions of some studies [34‒36], which concluded that the prevalence of dementia is reduced in patients who take lithium every day for a while compared to those who do not undergo lithium therapy and that regular lithium therapy may help patients to resist the onslaught of dementia. However, the results do not support the use of lithium to prevent dementia as they are inconsistent with some studies [18, 21, 37] that concluded that patients treated with lithium had a higher risk of being diagnosed with dementia compared to patients who did not receive lithium therapy [18], and could not prove that lithium therapy reduces the risk of dementia [37] or that lithium has a preventive effect on the development of dementia [21]. The possible reason for the discrepancy is the influence of other confounding factors in the study.…”
Section: Discussionmentioning
confidence: 94%
“…The use of lithium therapy has a protective effect on reducing the risk of developing dementia, which is consistent with the conclusions of some studies [34‒36], which concluded that the prevalence of dementia is reduced in patients who take lithium every day for a while compared to those who do not undergo lithium therapy and that regular lithium therapy may help patients to resist the onslaught of dementia. However, the results do not support the use of lithium to prevent dementia as they are inconsistent with some studies [18, 21, 37] that concluded that patients treated with lithium had a higher risk of being diagnosed with dementia compared to patients who did not receive lithium therapy [18], and could not prove that lithium therapy reduces the risk of dementia [37] or that lithium has a preventive effect on the development of dementia [21]. The possible reason for the discrepancy is the influence of other confounding factors in the study.…”
Section: Discussionmentioning
confidence: 94%
“…The same authors, analysing a cohort of almost 20,000 BD patients, found that lithium and lamotrigine did not increase the risk of stroke, whereas such a risk was higher with carbamazepine and valproate use (Chen et al, 2019). More recently, Ponzer et al (2023) showed that the use of lithium reduces the risk of cardiovascular and cerebrovascular disorders, while it increases such risks in relation to pulmonary artery embolism.…”
Section: { Review Of Key Literature From 2019 To 2023 On the Use Of L...mentioning
confidence: 99%
“…However, because elderly subjects are often excluded from randomized clinical trials, studies focused on the treatment of bipolar disorder in older age are lacking and the information is mainly based on data derived from mixed age populations [48,49]. A growing attention is being given to a subset of patients with bipolar disorder, defined "older age bipolar disorder" (OABD), i.e., bipolar patients aged 50 years and over with prevalent cognitive deficits, increased risk of dementia, impaired psychosocial functioning, frequent physical comorbidities, and premature death [50,51]. In a double-blind, randomized, controlled trial in elderly patients with bipolar disorder, lithium was more effective than valproate in reducing manic symptoms during a 9 week follow-up and both drugs were similarly well tolerated [52].…”
Section: Myth 1: Lithium Is Not the First Choice For Treating Patient...mentioning
confidence: 99%
“…Although caution is required when prescribing lithium to subjects with cardiovascular diseases, such as arrythmias and QT prolongation, especially with concomitant electrolyte imbalances [53], Ponzer et al [51] found a lower risk for cardiovascular and cerebrovascular diseases in BD patients receiving lithium.…”
Section: No Drug Has Antisuicidal Effects Lithium Has An Antisuicidal...mentioning
confidence: 99%